New Terms to Define the Field of Design - Alberto Bassi; Lucilla Calogero (DIID)

(untitled)
This paper presents the results of a research project undertaken by a team of researchers at the Università Iuav di Venezia, which began in January 2021 and ended in January 2023. The project investigated the present-day reality of design studios in the Veneto region, to understand the transformations that have occurred in the ways of thinking and acting tied to the modification of the areas of intervention and the design skills that are expected from the designers. The profession and relationships with companies and clients on the one hand have changed from familiar and historically-practiced approaches, reflecting transformations in the position and role of the designer, and on the other have undergone a significant expansion in the possibilities of intervention. The final goal of this study is to offer a reflection on the directions in which the profession is moving, with the aim of informing professionals and design businesses, as well as the educational institutions which are forming the next generations of designers.